Online cognitive behaviour training for the prevention of postnatal depression in at-risk mothers: a randomised controlled trial protocol - Jones, Bethany A (BioMed Central, 2013)
BACKGROUND: Postnatal depression (PND) is the most common disorder of the puerperium with serious consequences for both mother and child if left untreated. While there are effective treatments, there are many barriers for new mothers needing to access them. Prevention strategies may offer a more acceptable means of addressing the problem. Internet interventions can help overcome some barriers to reducing the impact of PND. However, to date there are no published studies that investigate the efficacy of internet interventions for the prevention of PND. METHODS/DESIGN: The proposed study is a two-arm double blind randomised controlled trial. 175 participants will be recruited in the immediate postnatal period at an Australian community hospital. Women who meet inclusion criteria (internet access, email address, telephone number, over 18, live birth, fluent English) will complete the Edinburgh Postnatal Depression Scale (EPDS). Those with a score above 9 will undertake the Structured Clinical Interview for DSM Disorders (SCID). Those with a clinical diagnosis of depression, or a lifetime diagnosis of bipolar disorder or psychosis on the SCID will be excluded. Following completion of the baseline battery women will be randomised using a computer-generated algorithm to either the intervention or control condition. The intervention will consist of 5 modules of automated, interactive cognitive behaviour training (CB training), completed weekly with email reminders. The control will replicate the level of contact participants experience with the intervention, but the content will be of a general health nature. Participants will complete questionnaires immediately post-intervention (6 weeks) and 3-, 6- and 12 months follow-up. There will also be a second SCID delivered via telephone at 6 months. We hypothesise that relative to the control group, the intervention group will show a greater reduction in postnatal distress on the EPDS (primary outcome measure). We also hypothesise that the intervention group will demonstrate lower levels of anxiety and stress and higher levels of parenting confidence than the control group following intervention and/or follow-up. DISCUSSION: The proposed study addresses a number of limitations of earlier trials. TRIAL REGISTRATION: Australia and New Zealand Clinical Trials Registers, ACTRN12609001032246.